2015
DOI: 10.1016/j.cgh.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concomitant Immunomodulator Therapy on Efficacy and Safety of Anti–Tumor Necrosis Factor Therapy for Crohn’s Disease: A Meta-analysis of Placebo-controlled Trials

Abstract: On the basis of a meta-analysis, continued use of immunomodulator therapy after starting anti-TNF therapy is no more effective than anti-TNF monotherapy in inducing or maintaining response or remission. RCTs are needed to adequately assess the efficacy of continued immunomodulator therapy after anti-TNF therapy is initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 36 publications
3
78
0
6
Order By: Relevance
“…Several studies have suggested that the risk of serious infection may not be increased with combination anti-TNF and immunomodulator therapy compared with anti-TNF monotherapy (8)(9)(10). However, combination therapy has been associated with an increased risk of opportunistic infection overall and herpes zoster in particular ( 9 ).…”
Section: Infections With CD Activity and Medicationsmentioning
confidence: 99%
“…Several studies have suggested that the risk of serious infection may not be increased with combination anti-TNF and immunomodulator therapy compared with anti-TNF monotherapy (8)(9)(10). However, combination therapy has been associated with an increased risk of opportunistic infection overall and herpes zoster in particular ( 9 ).…”
Section: Infections With CD Activity and Medicationsmentioning
confidence: 99%
“…104 105 therapy with an immunomodulator was no more effective than anti-TNF monotherapy for inducing six month remission, inducing a response, or maintaining a response in patients previously exposed to immunomodulators. 78 Subgroup analyses of individual anti-TNF agents showed a non-significant trend towards a benefit of combination therapy in achieving clinical remission at six months in patients treated with infliximab who had not previously been exposed to immunomodulators, but no such benefit was seen with adalimumab or certolizumab. 78 Caution must be used in interpreting these data because many of the patients included in the adalimumab and certolizumab trials had already not responded to infliximab.…”
Section: Postoperative Anti-tnf Prophylaxismentioning
confidence: 99%
“…78 Subgroup analyses of individual anti-TNF agents showed a non-significant trend towards a benefit of combination therapy in achieving clinical remission at six months in patients treated with infliximab who had not previously been exposed to immunomodulators, but no such benefit was seen with adalimumab or certolizumab. 78 Caution must be used in interpreting these data because many of the patients included in the adalimumab and certolizumab trials had already not responded to infliximab. Unfortunately, no direct comparative effectiveness trials are available.…”
Section: Postoperative Anti-tnf Prophylaxismentioning
confidence: 99%
“…In 2010, the SONIC trial showed superiority of combination therapy in achieving steroid-free clinical remission and mucosal healing as compared to monotherapy with azathioprine or infliximab [11]. Sequential combination therapy was not shown to be superior to monotherapy in a meta-analysis of six trials [12]. Another meta-analysis showed that combination therapy after failing a thiopurine was not beneficial over monotherapy with an anti-TNF agent, though fewer infusion reactions with infliximab were noted among those on combination therapy [13].…”
Section: 2mentioning
confidence: 99%